FORMULASI PENAMBAHAN KACANG MERAH (Phaseolus vulgaris L.) PADA PUDING JAMBU BIJI MERAH (Psidium guajava L.) SEBAGAI SUMBER ZAT BESI PENCEGAH ANEMIA WANITA USIA SUBUR (WUS) - Mega Saputri Ramadhani (2021)
Anemia related to a low level of hemoglobin under normal condition especially on woman of childbearing age. To prevent it, iron sources from red kidney beans could be the solution. Besides that, consuming red guava which contains Vitamin C can support to enhancer iron absorption. The main objective of this study was to formulate food sources of iron in the form of pudding using red kidney beans and red guava to prevent anemia. This study used an experimental method with a completely randomized design (CRD). The comparison of red guava puree and red kidney bean puree from three level, that is F1 (100 gr: 46 gr), F2 (100 gr: 56 gr), and F3 (100 gr: 66 gr). The selected formula in F3 has a water content of 88,36%, an ash content of 0,20%, a protein content of 0,80%, a fat content of 0,30%, a carbohydrate content of 10,33% and an iron content amounted to 5,47 mg.